PENGARUH POLA ASUH DEMOKRATIS DENGAN INTERAKSI SOSIAL ANAK PRA SEKOLAH DI DESA BULILA - Rahmawaty Parman; Annisa Safitri Ahmad (program studi psikologi, 2023)
Children's social interaction skills develop according to the stages of their developmental age. The achievement of the stage of social development requires the role of parents in providing stimulation that affects the child's social interaction ability. Parenting provided by parents is able to become a model in learning children's behavior from parent figures, therefore children can apply how to interact and have reciprocal relationships with friends their age. This research aims to determine the effect of democratic parenting with the social interaction of pre- school children with the research location in Bulila Telaga Village. This type of research is quantitative, with a sample of 40 parents. The instrument used is a scale of democratic parenting and a scale of social interaction of pre-school children. With purposive sampling technique, the data analysis used was simple linear regression analysis. With the results there is an influence of democratic parenting with social interaction of pre-school children with a value of 0.003. Based on the calculation analysis in this research, it was obtained from the t count of -3.196 while the ttable value of 2.021 thus H0 was rejected and H1 was accepted, that there is an influence of democratic parenting on social interaction.